Role of therapeutic endoscopic retrograde cholangiopancreatography in treatment of pancreaticobiliary diseases - JIANG Shengjun (Linchuang Gandanbing Zazhi, 2016)
ObjectiveTo investigate the effect of therapeutic endoscopic retrograde cholangiopancreatography (ERCP) on liver function and treatment outcome in patients with pancreaticobiliary diseases. MethodsA total of 397 patients with pancreaticobiliary diseases who underwent ERCP with an electronic duodenoscope in Beijing Chuiyangliu Hospital from January 2005 to July 2015, were enrolled. According to the type of disease, they were divided into benign obstruction group (109 patients), malignant obstruction group (47 patients), pancreatitis group (27 patients), foreign body obstruction group (127 patients), simple cholangitis group (19 patients), biliary fistula group (15 patients), juxta-ampullary duodenal diverticula group (29 patients), and liver transplantation group (24 patients). Liver function parameters including alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), γ-glutamyl transpeptidase (GGT), and total bilirubin (TBil) were measured at 1 day before ERCP and at 4 weeks after ERCP. The therapeutic effect was evaluated at 1 month after ERCP. The paired t-test was used for comparison of continuous data before and after treatment within one group, an analysis of variance was used for comparison between multiple groups, and the chi-square test was used for comparison of categorical data between groups. ResultsAfter ERCP, all the patients showed significant improvements in ALT, AST, ALP, GGT, and TBil, suggesting that ERCP significantly improved the subjects′ liver function (all P＜0.05). The evaluation of therapeutic effect showed that after ERCP, all the groups showed significant remission of symptoms; all the patients in the simple cholangitis group were cured, while those in the liver transplantation group and malignant obstruction group only achieved certain improvements. ConclusionTherapeutic ERCP can significantly improve the patients′ liver function. However, as for patients with liver transplantation and pancreaticobiliary tumors, laparoscopic surgery should be performed in combination with ERCP.